PERANAN TEKNIK SPLIT-BOLUS TERHADAP KUALITAS CITRA PADA PEMERIKSAAN MSCT LEHER - Lustyana Devi, Hefty; Safarini, Bekti; Sulaksono , Nanang (Perhimpunan Radiografer Indonesia (PARI), 2020)
Background : According to the theory, Neck MSCT examination were performed using monophasic injection techniques. Split-bolus is an innovative technique that divides intravenous (IV) contrast media into two or three boluses and combines phase images in single scanning. The MSCT split-bolus scan with a combination of parenchymal and vascular enhancement is a valid alternative approach compared to the standard monophasic MSCT protocol. The purpose of this study was to determine the split-bolus technique in neck MSCT examination and its role in the quality of the image. Method : This research is a descriptive qualitative study with a literature review study method. Data is collected by the documentation method. The electronic database was searched using the keywords